Qualitative Traits of Muscovy duck (Cairina moschata) in Ciayumajakuning, West Java, Indonesia - dini widianingrum (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2022)
Qualitative traits can be used as a reference for entog development and conservation. Qualitative traits are indispensable for selection based on phenotypics such as plumage color, beak color, and shank color. The research objective was studied the qualitative traits of entog in Ciayumajakuning (Cirebon, Indramayu, Majalengka, dan Kuningan). This research uses survey method with sampling technique of multistage probability random sampling. The research object observed are 673 Muscovy ducks consisting of 309 drake and 364 duck. Data analysis applies descriptive qualitative analysis method. The results of research show that duck Muscovy ducks plumage colors are dominated by black and white (44.78%), only white (28.30%), and only black (17.86%); while drake are dominated by only white (45%), black and white (35.9%), and gray (7, 77%). The duck beak colors are dominated by black (25.82%), black and white (20.60%), and pink (23.63%); while drake beak colors include pink (38.80%), black (21.00%), and black and white (19.40%). Duck shank colors are dominated by black (39.29%), white (27.29%), and yellow (18.68%); while drake shank colors, among others, are yellow (41.70%), black (29.80%), black and white (12.00%). Based on the results of the study, it can be concluded that the qualitative traits of Muscovy duck in Ciayumajakuning are quite diverse.